Pelatihan Manajemen Kedaruratan Dasar Bagi Kader Kesehatan: Basic Emergency Management Training for Health Cadres - Kamesyworo, Kamesyworo; Hartati, Sri; Haryant, Eka (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Emergency situations are sudden events that require immediate action. These conditions can arise from trauma or non-trauma incidents, with risks of respiratory arrest, cardiac arrest, organ damage, or bleeding. Emergencies can occur to anyone, at any time, and anywhere, characterized by their rapid onset and unpredictability. Quick, accurate, and careful management of emergencies is crucial to prevent death and disability, in line with the principle that "time is life." Health education is one of the strategic steps to enhance public awareness in facing emergency situations, especially through community service activities aimed at providing practical understanding of emergency management. This community service activity was conducted in Sari Bunga Mas Village and involved 26 participants, including community cadres and the general public. The methods used included a pre-test to assess participants' initial knowledge, lectures to provide information about emergencies, demonstrations to show practical emergency management procedures, distribution of leaflets as supplementary materials, and a post-test to evaluate the increase in participants' knowledge. Data from the pre-test and post-test were analyzed to measure the effectiveness of the intervention. The activity was attended by cadres and the community of Sari Bunga Mas Village, totaling 26 people. Data analysis showed the following results: before the intervention, 12% of participants had good knowledge, and after the intervention, there was an increase to 79.2% with good knowledge, with the remaining participants showing moderate knowledge. This activity successfully demonstrated that health education with an interactive approach significantly improves the community's knowledge about basic emergency management. The lecture provided a deep theoretical understanding, while the demonstration helped participants learn practical steps they can take in emergency situations. The distribution of leaflets served as a reminder and additional reference for the participants.